Close linkage of a gene for X linked deafness to three microsatellite repeats at Xq21 in radiologically normal and abnormal families. Issue 12 (December 1994) - Bitner-Glindzicz, M; de Kok, Y; Summers, D; Huber, I; Cremers, F P; Ropers, H H; Reardon, W; Pembrey, M E; Malcolm, S
Abstract : We have used three highly polymorphic microsatellite repeats from Xq21 to type families in whom a gene for X linked deafness with perilymphatic gusher (DFN 3) was segregating. All three markers were tightly linked to the disease in its radiologically normal and abnormal forms, with a maximum lod score of 10.37 with DXS995 and 8.44 with DXS986 at zero recombination, and 14.03 with DXS1002 at theta = 0.01. In an isolated case of deafness of this type, DXS995 indicated either the first recombination observed between the marker and the disease gene or a new mutation in the proband. Southern blotting using a cosmid fragment from the candidate region has confirmed a de novo mutation by showing a deletion in the proband which is not present in his mother as judged by dosage analysis. We also describe a family with a paracentric inversion associated with a microdeletion and discuss how deletion mapping using these and other markers in the region has helped to define a candidate region for the gene.